Cuba in quarantine: Images of precarity and vulnerability during the COVID-19 pandemic - Suquet, Mirta (2023)
This research paper examines the artistic creations emerging from Cuba, focusing on the profound impact of COVID-19 on the island. Alongside investigating the social, economic, and health ramifications triggered by the health crisis, the study scrutinizes the official narratives surrounding the pandemic. Its aim is to shed light on how these narratives tend to overlook the most vulnerable segments of the population. In response to these omissions, the artistic works delve into the spaces and subjects that bring forth the precarious existence shaped by the pandemic and the shortcomings of the Cuban state.